Analysis and Study on Crack Characteristics of Highway Tunnel Lining - Zhang, Nian; Zhu, Xuejian; Ren, Yifan (Salehan Institute of Higher Education, 2019)
Lining cracks are one of the most common diseases in highway tunnels, and the existence of lining cracks directly affects the overall stability and durability of tunnels, which has an important impact on the safe operation of tunnels, and it is necessary to analyze and study the characteristics of tunnel lining cracks. Combining with the detection data of multiple highway tunnels in the field, the different types of tunnel cracks are divided, and the classification numerical statistics method is used to obtain that the number and length of annular cracks in highway tunnel cracks are significantly higher than those of the other two kinds of cracks, and the longitudinal cracks in tunnel crack cracking degree are greater than the circumferential cracks and the inclinded cracks. The influence degree of cracks on the safety of tunnel structure longitudinal cracks are relatively the largest, the inclinded cracks are second only to longitudinal cracks, and the influence of cyclic cracks is relatively small. It provides reference for tunnel engineering design, construction, operation management and comprehensive improvement work.